Genetic and Evolutionary Computation – GECCO 2004 : Genetic and Evolutionary Computation Conference, Seattle, WA, USA, June 26-30, 2004. Proceedings, Part I - Deb, Kalyanmoy; SpringerLink (Online service) (Lecture Notes in Computer Science, ISSN 0302-9743, 2004)
The two volume set LNCS 3102/3103 constitutes the refereed proceedings of the Genetic and Evolutionary Computation Conference, GECCO 2004, held in Seattle, WA, USA, in June 2004. The 230 revised full papers and 104 poster papers presented were carefully reviewed and selected from 460 submissions. The papers are organized in topical sections on artificial life, adaptive behavior, agents, and ant colony optimization; artificial immune systems, biological applications; coevolution; evolutionary robotics; evolution strategies and evolutionary programming; evolvable hardware; genetic algorithms; genetic programming; learning classifier systems; real world applications; and search-based software engineering.
Keywords: Computer science; Microprocessors; Computers; Algorithms; Computer science : Mathematics; Artificial intelligence; Bioinformatics; Computer Science; Computation by Abstract Devices; Algorithm Analysis and Problem Complexity; Artificial Intelligence (incl. Robotics); Processor Architectures; Discrete Mathematics in Computer Science